A Proteomic Approach to the Identification of Lung Cancer Markers. Issue 4 (13th June 2013) - Hanash, Samir; Brichory, Franck; Beer, David
Abstract : We have developed a comprehensive approach to the identification of protein markers in lung cancer that includes profiling of tumor tissue and cell lines as well as the analysis of serum for autoantibodies to lung tumor antigens. A large number of proteins that are differentially expressed in the major subtypes of lung cancer have been identified by mass spectrometry. A database of protein expression in lung cancer and other types of cancer has been constructed that integrates two-dimensional gel profiles, mass spectrometry data, quantitative protein data and gene expression data at the RNA level, that serves as a resource for biomarker identification. Analysis of the serological response in lung cancer has led to the identification of novel markers detectable in serum of lung cancer patients at the time of diagnosis. The proteomic approach is likely to yield novel classification schemes and novel markers for early diagnosis of lung cancer.